Emission Characteristics of Heavy-Duty Vehicle Diesel Engines at High Altitudes - Y. M. Zheng; L. B. Xie; D. Y. Liu; J. L. Ji; S. F. Li; L. L. Zhao; X. H. Zen (Journal of Applied Fluid Mechanics, 2023)
The aim of this study was to accurately quantify the emission characteristics of pollutants at different altitudes. We used an intake and exhaust altitude simulation system that could simulate the intake and exhaust pressures of a national sixth vehicle diesel engine at different altitudes. Experimental research was conducted on the World Harmonized Transient Cycle (WHTC) and World Harmonized Steady State Cycle (WHSC) of the diesel engine. The results showed that carbon monoxide (CO) emissions increased with the altitude at full load, but their rates were significantly reduced at low speed (800 rpm), increasing by 0.0084–0.665 ppm/m. Hydrocarbon (HC) emissions showed an initial decreasing and then increasing trend, with a rise of up to 30%. Nitrogen oxides (NOx) showed a linear decreasing trend, especially at low speed. With the increase in altitude, the cycle work of the diesel engine decreased in a non-linear manner, and the decrease became more pronounced above 3000 m. The raw emission results of the WHTC and WHSC tests also revealed that CO increased exponentially, NOx decreased slightly and then increased rapidly, HC increased linearly, and the emissions of all pollutants deteriorated significantly above 3000 m. The exhaust emission results of the WHTC and WHSC tests showed that the CO emission showed an initial decreasing and then increasing trend with the elevation of the altitude, approximately 15 ± 5 mg/kWh. HC emissions showed an increasing trend, with HC emissions of 3 – 6 mg/kWh for the WHTC and 1 – 2 mg/kWh for the WHSC. NOx emissions did not follow any obvious rule, while the particulate matter (PM) tended to increase and then decrease with the elevation of the altitude. In relation to the current emission standards, the limit value margin for CO and HC exhaust emissions is greater than 95% and the limit value margin for PM emissions is greater than 88% at an altitude of 4000 m. The NOx emission limit is greater than 87% (within 3000 m), but there is a risk of exceeding the limit above 3000 m. The second sampling data from the WHTC and WHSC showed that the raw emissions of the engine were higher in the high-altitude area than in the low-altitude area, but the change law of the exhaust emissions was not obvious, and the levels of both emissions were low.